Tracking of serum lipid levels from childhood to adulthood: Systematic review and meta-analysis - Stanesby, Oliver (Elsevier, 2025)
Background and aims: The utility of lipid screening in pediatric settings for preventing adult atherosclerotic cardiovascular diseases partly depends on the lifelong tracking of lipid levels. This systematic review aimed to quantify the tracking of lipid levels from childhood and adolescence to adulthood.
Methods: We systematically searched MEDLINE, Embase, Web of Science, and Google Scholar in March 2022. The protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO; ID: CRD42020208859). We included cohort studies that measured tracking of lipids from childhood or adolescence (<18 years) to adulthood (≥18) with correlation or tracking coefficients. We estimated pooled correlation and tracking coefficients using random-effects meta-analysis. Risk of bias was assessed with a review-specific tool.
Results: Thirty-three studies of 19 cohorts (11,020 participants) were included. The degree of tracking from childhood and adolescence to adulthood differed among lipids. Tracking was observed for low-density lipoprotein cholesterol (pooled r = 0.55-0.65), total cholesterol (pooled r = 0.51-0.65), high-density lipoprotein cholesterol (pooled r = 0.46-0.57), and triglycerides (pooled r = 0.32-0.40). Only one study included tracking of non-high-density lipoprotein cholesterol (r = 0.42-0.59). Substantial heterogeneity was observed. Study risk of bias was moderate, mostly due to insufficient reporting and singular measurements at baseline and follow-up.
Conclusions: Early-life lipid measurements are important for predicting adult levels. However, further research is needed to understand the tracking of non-high-density lipoprotein cholesterol and the stability of risk classification over time, which may further inform pediatric lipid screening and assessment strategies.